Foreign Trade Representative Strategy In Building The Image Of Indonesian Products In Australia - Febyanti Juliastica; Akim Akim; Teuku Rezasyah (UNIVED Press, 2024)
Trade relations between Indonesia and Australia have been around for a long time. This is proven by the commitment of the two countries to improve trade relations. However, in 2020 trade between the two countries experienced a significant decline due to the Covid-19 pandemic. As representatives of Indonesian trade in Australia, the trade attaché and the Indonesia Trade Promotion Center (ITPC) are crucial institutions in bridging trade between the two countries. So, this research aims to discuss the strategy of Indonesian trade representatives in Australia in building the image of Indonesian products. This research uses qualitative research methods and data collection with literature studies such as previous research, books, and official documents, the concept used is economic diplomacy in analyzing problems. The results of this research show that the strategy of Indonesian trade representatives in Australia was carried out in several stages, namely economic salesmanship, economic networking, image building, and regulatory management.